O5A.3 Injured at work: factors predictive of further work-related injuries – a prospective study. (April 2019) - Harcombe, Helen; Samaranayaka, Ari; Wyeth, Emma H; Davie, Gabrielle; Cameron, Ian D; Derrett, Sarah
Abstract : Background: Work-related injuries can have a large impact on employees, employers and wider society. Preventing subsequent work-related injuries from occurring among those who have already had a work-related injury has the potential to reduce the burden of work-related injuries. However, predictors of subsequent work injuries must first be understood. This study investigates New Zealand participants from the Prospective Outcomes of Injury Study (POIS) with a substantial work-related injury (the 'sentinel' injury) and examines subsequent work-related injury events occurring during the following 24 months. Objectives are to: 1) describe the nature of sentinel and subsequent work-related injuries, and 2) examine work-related predictors of subsequent work-related injuries. Methods: Of the 2856 POIS participants, 754 were recruited following a substantial work-related injury. Data were combined from: 1) participant interviews approximately 3 months following their sentinel injury, 2) administrative claims data from New Zealand's universal no-fault injury insurer (the Accident Compensation Corporation), and 3) hospital discharge data to 24 months. Predictors of subsequent work-related injuries were examined using multivariable analyses. Results: Work-related sentinel injury events most commonly involved spine dislocations/sprains/strains (25%) with 'lifting/loading/pulling' the most common work task involved. One third (34%; n=258) went on to have at least one subsequent work-related injury in the following 24 months. Of those whose sentinel work-related injury was related to 'lifting/loading/pulling', 19% had at least one subsequent work-related injury event also related to this type of task. Predictors examined included pre-sentinel injury job strain, social support from colleagues and supervisors, physical work tasks, job security and job satisfaction. Conclusion: A substantial proportion of participants with a work-related sentinel injury had further work-related injuries in the following 24 months. The identification of factors that predict those at risk of subsequent work-related injuries could provide a useful focus for those involved in the rehabilitation of people with work-related injuries.